تطوير إدارة التعليم التمريضي في مصر على ضوء الخبرة الفلبينية - زناتي، أمل محسوب محمد (جامعة سوهاج - كلية التربية, 2022)
يستهدف البحث تطوير إدارة التعليم التمريضي بالعمليات، الثلاث: القبول، والجودة والاعتماد، والترخيص على ضوء الخبرة الفلبينية، وقد تم استخدام المنهج الوصفي في الدراسات المقارنة، وتم الاستعانة بأداة المجموعة البؤرية؛ لجمع معلومات كيفية عن واقع إدارة التعليم التمريضي في مصر، ويتضمن البحث النقاط التالية: الإطار العام للبحث، والإطار النظري لإدارة التعليم التمريضي، وخبرة الفلبين في إدارة التعليم التمريضي، ثم واقع إدارة التعليم التمريضي في مصر، للتوصل إلى بعض الإجراءات المقترحة لتطوير إدارة التعليم التمريضي في مصر على ضوء الخبرة الفلبينية، بما يتوافق مع البيئة المصرية. وفيما يلي بعض الإجراءات المقترحة لتطوير إدارة التعليم التمريضي في مصر طبقا لمحاور البحث: أولا- القبول، يقترح في هذا المحور: تطوير معايير القبول بالتعليم التمريضي، وتفعيل نتائج اختبار القدرات، وتطوير اختبارات السمات الشخصية، وعقد اختبارات القبول للطلاب المرشحين إلكترونيا، لتحديد مدى ملاءمة المتقدم للدراسة بالكلية تحت إشراف كليات التمريض، ولجنة القطاع بالمجلس الأعلى للجامعات، ووزارة الصحة والسكان. ثانيا- الجودة والاعتماد، من الإجراءات المقترحة في هذا المحور: عقد بروتوكول تعاون مع كليات التمريض الفلبينية المعتمدة، لتبادل الخبرات في: تقليل الفجوة بين الدراسة النظرية، والدراسة العملية للتمريض، وزيادة فرص التدريب السريري؛ بما يلبي احتياجات السوق المحلي والإقليمي والعالمي، وعقد اتفاقات دولية لتصدير الكوادر التمريضية؛ بما يضمن الحفاظ على حقوقهم، والقيام بواجباتهم، وعقد ندوات تثقيفية عن دور التمريض في خدمة المجتمع. ثالثا- الترخيص، يقترح في محور الترخيص: تطبيق اختبار للترخيص، كمؤشر مناسب لتوافر الحد الأدنى من الكفاءة للخريج الجديد، وتحديث منظومة الترخيص بما يتناسب مع المضمون العلمي، والمهاري، والأخلاقي لخريجي التعليم التمريضي باختلاف مستوياته، وبما يتناسب مع الكفايات التي يكتسبها طلاب التمريض، إلى جانب إتاحة فرص دراسية في مجال التمريض للدول المتقدمة، ومنها: الفلبين. This research aimed to develop nursing education management through its three phases, namely, admission, quality and accreditation, and licensing in Egypt based on the Filipino experience. It utilized the Descriptive method in the Comparative research using focus group for collecting qualitative data about the status quo of nursing education management in Egypt. The research includes the following: The general framework of the research, the theoretical framework for nursing education management, the status quo of nursing education management in the Philippines and Egypt, followed by the suggested procedures to develop nursing education management in Egypt in the light of the Filipino experience. The research also reports the viewpoints of nursing experts in line with the Egyptian environment. Among the suggested procedures for developing nursing education management in Egypt according to the research sections are: 1- In the admission phase, the study suggested developing admission criteria of nursing education, activating the results of the aptitude test, developing personality trait tests, and holding admission e-tests for nominated students to determine the suitability of the applicant to study under the supervision of the Nursing Faculties, the Sector Committee of the Supreme Council of Universities, and the Ministry of Health and Population. 2- In quality and accreditation, The study suggested conducting a cooperation protocol with accredited Filipino nursing colleges to share experiences in: reducing the gap between theoretical and practical studies of nursing, and increasing opportunities for clinical training in order to meet the needs of the local, regional and global market, conduct international agreements to export nursing cadres, as well as to ensure that their rights are preserved, their duties are carried out, and educational seminars are held on the role of nursing in community service. 3- In licensing, The study suggested applying a licensing test as a registered nurse to be considered as an appropriate indicator of the new graduate competence, and updating the licensing system in line with the scientific, skill and affective content of graduates of nursing education at all levels in line with the competencies acquired by nursing students, in addition to providing opportunities for scholarships in the field of Nursing for advanced countries in this field, including the Philippines.
Keywords: التعليم التمريضي -- الاعتماد الأكاديمي -- جودة التعليم -- الخبرة الفلبينية -- مصر